Elasticidades parciais e totais de demanda e oferta de carnes bovina e suína no mercado brasileiro - Gomes Lobato , Jorge; Brandt, Sergio Alberto; Aad Neto , Alexandre; Martins Rezende , Alberto; Oliveira, Marcília B M (Revista Ceres, 2025)
The major objective of this study is the analysis of the Brazilian pork and beef markets based on a simultaneous equation model of supply and demand and estimated by two stages least squares.